Physical Downlink Control Channel format selection of evolved node B in Long Term Evolution system - Jia Luo; Xiaowen Li (2012 5th International Conference on Biomedical Engineering and Informatics, 2012)
In TD-LTE (Time Division-Long Term Evolution) system, Control Channel Element (CCE), which transmits control information, is the resource element mapping unit of Physical Downlink Control Channel (PDCCH). It is used by uplink and downlink schedulers. Rational utilization of CCE resources and choose appropriate aggregation of one or several consecutive CCEs to transmit Downlink Control Information (DCI) have significant impact on success ratio of User Equipment (UE) blind detection and system performance. In this paper, one modified method which is based on reported Channel Quality Indicator (CQI) by UE to make selection of CCE aggregation is proposed. Its implementation complexity is very low. The simulation results show the modified method improves the success ratio of UE blind detection and the CCE resources utilization. At the same time, the feasibility and effectiveness of this modified method have been verified.